2023
DOI: 10.1128/spectrum.00322-23
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Reveals Compositional and Functional Microbial Changes Associated with Osteoporosis

Abstract: Osteoporosis is the most common metabolic bone disease associated with aging. Mounting evidence has linked changes in the gut microbiota to the pathophysiology of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…As such, our results are the first to demonstrate that DP treatment for 8 weeks in female mice reduces the relative abundance of Clostridium sensu stricto 1 present within the fecal microbiome from approximately 10% to zero, and there is a strongly significant negative correlation between the relative abundance of Clostridium sensu stricto 1 and distal femur trabecular BV/TV%. In addition, our results support what has previously been reported in the literature, with reductions in the relative abundance of Clostridium sensu stricto 1 being associated with improvements in bone health ( Akinsuyi and Roesch, 2023 ). Future studies will be necessary to better understand the role of Clostridium sensu stricto 1 and the role that this group of bacteria plays in mediating bone health in not only this model of GIO, but bone health in general.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As such, our results are the first to demonstrate that DP treatment for 8 weeks in female mice reduces the relative abundance of Clostridium sensu stricto 1 present within the fecal microbiome from approximately 10% to zero, and there is a strongly significant negative correlation between the relative abundance of Clostridium sensu stricto 1 and distal femur trabecular BV/TV%. In addition, our results support what has previously been reported in the literature, with reductions in the relative abundance of Clostridium sensu stricto 1 being associated with improvements in bone health ( Akinsuyi and Roesch, 2023 ). Future studies will be necessary to better understand the role of Clostridium sensu stricto 1 and the role that this group of bacteria plays in mediating bone health in not only this model of GIO, but bone health in general.…”
Section: Discussionsupporting
confidence: 91%
“…In the random forest models, Clostridium sensu stricto 1 was the third most important genus in both classifying samples into appropriate groups as well as in the regression model to predict BV/TV%. A recent meta-analysis analyzing gut 16S rRNA amplicon data from patients in China and South Korea revealed that Clostridium sensu stricto 1 was significantly elevated in patients with osteoporosis ( Akinsuyi and Roesch, 2023 ). To our knowledge, there have not been previous reports demonstrating the relation between Clostridium sensu stricto 1 and GIO or DP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing evidence of significant differences in gut microbiota composition and metabolic function in patients with urticaria compared to healthy populations ( Lu et al., 2019 ; Wang et al., 2021 ; Zhang et al., 2021 ), our study showed for the first time a significant correlation between increased abundance of the genus Intestinibacter and the risk of urticaria development, which was statistically significant even after FDR correction. There is limited research on this flora constituent, and studies have reported that the abundance of Intestinibacter is associated with type 2 diabetes mellitus ( Neri-Rosario et al., 2023 ), Crohn’s disease ( Forbes et al., 2018 ), prenatal depression ( Fang et al., 2023 ), and osteoporosis ( Akinsuyi and Roesch, 2023 ) and is also influenced by the HLA genotype ( Forbes et al., 2018 ), but its definitive role remains unknown. Functional analysis of Intestinibacter has shown that it is able to degrade fucose, suggesting an indirect involvement in intestinal mucus degradation ( Mueller et al., 2021 ), leading to a compromised intestinal barrier that allows microbes and toxins to infiltrate the body’s circulation and skin, triggering an immune response; however, whether there is a link between this activity and the development of urticaria remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are also reported to attenuate age-related bone loss by increasing the relative abundance of SCFA producing bacteria in the gut, which was reflected by the significantly increased concentration of SCFA measured in the stool of aged mice that consumed probiotics [ 42 ]. The mechanism by which SCFAs reduced bone resorption is closely associated with increased intestinal calcium absorption, osteoblast differentiation, and decreasing osteoclast activity [ 43 , 44 ]. Similarly, Yuan et al [ 45 ] observed that Bacteroidetes vulgatus probiotic treatment restored gut microbial composition and subsequently downregulates the Lipopolysaccharide/TLR-4/p-NF-κB pathway.…”
Section: Factors That Alter the Gut Microbiotamentioning
confidence: 99%